Neuropsychological evaluation and parental assessment of behavioral and motor difficulties in children with neurofibromatosis type 1. (January 2016) - Coutinho, V.; Kemlin, I.; Dorison, N.; Billette de Villemeur, T.; Rodriguez, D.; Dellatolas, G.
Highlights: Children with NF1 present specific motor and visuomotor difficulties. Verbal IQ was higher than Performance IQ. All parental behavioral questionnaires were strongly inter-correlated. Parental questionnaires were wickedly associated with neuropsychological tests. Cognitive difficulties were more marked in familial than in sporadic NF1 forms. Abstract: Neurofibromatosis type 1 (NF1) is an autosomal dominant multisystem disorder, with large inter and intrafamilial clinical variability and uncertain prognosis. In children with NF1 cognitive disorders, learning difficulties and behavioral problems are common. The present study aims to establish the neuropsychological and behavioral profiles of 78 patients with NF1, aged between 5 and 18 years, and to examine the relationship between these profiles and the transmission of NF1 (sporadic vs. familial), clinical manifestations, and environmental factors. We used several questionnaires completed by parents and neuropsychological tests. The results confirmed specific neuropsychological disabilities in children with NF1, especially involving visuospatial and fine motor skills, learning difficulties and behavioral problems. Cognitive difficulties were significantly more frequent in patients with familial than in those with sporadic NF1. All parental questionnaires were correlated with each other, but parental reports were not associated with FSIQ, SES, school status, and clinical manifestations of the disease. Neuropsychological tests were poorly related to parental reports of cognitive and behavioral difficulties.